Quality of Arumanis Mango Fruit Due To Heat Treatment and Waxing - Yulianti, Hesti; Wulandani, Dyah; Hasbullah, Rokhani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Production of Arumanis mango shows an increase, however to meet the needs of the export markets, quarantine regulations are hampered because mango is a host for fruit flies. The combination of hot water treatment (HWT) and waxing is an alternative for fruit fly disinfestation and maintaining quality. The purpose of this study was to determine the effect of HWT and waxing on the quality of Arumanis mango. Arumanis mangoes at 85% maturity were obtained from farmers in Cirebon having average weight of 400-450 g. The HWT was carried out at 47.0Â°C for 65 minutes and 75 minutes then waxing the fruit in: 1.5% chitosan (P1), 6% beeswax (P2) and a combination of beeswax 6% + chitosan 1.5% (P3). After the treatment, the fruit quality was analyzed every 4-day including hardness, weight loss, total soluble solids, color, respiration rate, total plate count, and organoleptic test. The best treatment was HWT at 47.0Â°C for 65 minutes and waxing using a combination of beeswax and chitosan. This combination treatment resulted in fruit quality with hardness was 1.72 kgf weight loss of 0.05%; total dissolved solids of 13.4Â°Brix; and color L* a* b*, of respectively 43.9 ;16.7; 28.2, the respiration rate of 5.2Â ml O2/kg.h and CO2 production were of 7.1 ml CO2/kg.h and total plate count of 1.25 Ã— 103 CFU/ml. Â Keywords:Â Arumanis mango, Heat treatment, Hot water treatment, Waxing, Quality